Peronism, engineers and students. The conflict between the national workers’ university and the engineering institutions in argentina (1955-1959) - Koc Muñoz, Álvaro Sebastián (Historia y Memoria de la Educación, 2023)
The purpose of this paper is to analyze the confrontation that occurred between the entire academic community of the Universidad Obrera Nacional (National workers’ University, UON) and the various institutions of the engineering profession during the so-called “struggle for autonomy and hierarchization of the National Technological University (UTN)”.This conflict began with the emergence of the self-styled “Liberating Revolution” (1955) in power and culminated with the passing of Law 14,855 (1959) that established the change of name, structure and operation of the UON. In this sense, the article will seek to trace the development of this conflict and the political positions of the different professional associations within its framework. By way of hypothesis, we maintain that the central factor in the failure to resolve the problem involving the UON during the military government that succeeded Peronism was the considerable pressure exerted by both blocs – professional associations and supporters of the “UTN” – which led to a “zero sum game” in which neither side could impose its position over the other. This conflict would finally find its outcome with the arrival of the Frondizi government, which included the “UTN” within its political agenda. Finally, it should be noted that this study will be carried out using different documentary sources not worked on until now, among which the press of the time and documentation from various institutions stand out.